Upaya Peningkatan Pengetahuan dan Perilaku Cuci Tangan Pakai Sabun(CTPS) pada Masyarakat Pemulung di Tempat Pembuangan Akhir Desa Sihom Kec. Indrapuri Aceh Besar - Diana Lestari; Meylissa (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
The aim of this community service is to produce a community of scavengers with clean and healthy living habits (PHBS) through washing hands with soap (CTPS). Because in final disposal areas or what can be called landfills, there is always a lot of dirt, starting from food waste and other waste. Hand washing, namely washing hands with soap, has been proven to be effective in preventing transmission of the corona virus because clean hands after washing with soap can reduce the risk of the virus entering the body. The method used was socialization and providing training to the community to live healthy lives. This activity lasted for 3 days and collaborated with the village midwife and the Indrapuri Community Health Center UPT Aceh Besar. The results of the service obtained from this activity are that the TPA community is happy to hold this activity and provide a basis for lay people who do not understand healthy living by washing their hands. This activity is very useful and has an impact on society. The conclusion of this activity is for the community to provide knowledge and provide appropriate assistance to the community for the sake of health